2012
DOI: 10.1111/j.1460-9592.2012.03905.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of severely obese children undergoing tonsillectomy

Abstract: Background Sleep-disordered breathing, a common condition in obese children, is a frequent indication for tonsillectomy. Objective The purpose of this study was to examine the association between obesity and perioperative complications in children undergoing tonsillectomy. Methods/Materials A sample of 100 severely obese children (body mass index for age, BMIA, ≥98th percentile) between ages 2 to 18 years who underwent tonsillectomy at Mayo Clinic Rochester was randomly selected. Each severely obese child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 22 publications
3
22
3
3
Order By: Relevance
“…17,22 Obesity has been shown to be a significant risk factor for postoperative complications in children post-AT. [23][24][25][26] Interestingly, we did not find a similar association in our study. 27 One possible explanation for this is most of our study children had a BMI less than 30 kg/m 2 plus they did not have any other comorbidities.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…17,22 Obesity has been shown to be a significant risk factor for postoperative complications in children post-AT. [23][24][25][26] Interestingly, we did not find a similar association in our study. 27 One possible explanation for this is most of our study children had a BMI less than 30 kg/m 2 plus they did not have any other comorbidities.…”
Section: Discussioncontrasting
confidence: 84%
“…Obesity has been shown to be a significant risk factor for post‐operative complications in children post‐AT . Interestingly, we did not find a similar association in our study .…”
Section: Discussioncontrasting
confidence: 83%
“…14 In a matched case-control study of tonsillectomy patients, severely obese children with or without OSA had a higher risk for peri-operative complications than normal weight controls. 15 The authors considered that both severe obesity itself and systemic co-morbid conditions in obese children contributed to the observed higher complication rate. Overall, the literature consistently indicates an increased risk for respiratory problems following tonsillectomy, at least in overweight children.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are several reports showing increased respiratory complications during perioperative and postoperative periods following AT in obese children, although these reports are retrospective and observational studies. [5][6][7][8] Two prospective studies evaluating polysomnographic findings immediately after AT yielded conflicting results. 9,10 Both studies failed to specifically assess obese children.…”
mentioning
confidence: 99%
“…One previous study suggested that obesity was a risk factor for postoperative respiratory complications following AT independent of sleep-disordered breathing, but the subjects in that study were severely obese children. 8 How long do we need to monitor these children? Prior studies have shown that apnea and desaturation may not be apparent until 5 to 18 hours postoperatively, partly due to alteration in timing of rapid eye movement sleep.…”
mentioning
confidence: 99%